Emerging role of SIRT3 in endothelial metabolism, angiogenesis, and cardiovascular disease. Issue 3 (21st August 2018) - He, Xiaochen; Zeng, Heng; Chen, Jian‐Xiong
Abstract: Sirtuin 3 (SIRT3) a mitochondrial enzyme that plays an important role in energy homeostasis, cardiac remodeling, and heart failure (HF). The expression of SIRT3 declines with advanced age, cardiovascular, and metabolic diseases. Accumulating evidence suggests that SIRT3 plays a critical role in protecting the heart from cardiac hypertrophy, cardiac dysfunction associated with HF, and in the protection of cardiac cells from stress‐mediated cell death. Clinical studies have demonstrated that HF with preserved ejection fraction (HFpEF) in patients present with abnormalities in coronary microcirculation related to endothelial dysfunction and coronary microvascular rarefaction. Although SIRT3‐mediated regulation of mitochondrial homeostasis and heart function has been intensively investigated, the effect of SIRT3 on endothelial cell (EC) glycolytic metabolism and microvascular function has not been well studied. ECs utilize glycolysis for generating ATP rather than oxidative phosphorylation to maintain their normal functions and promote angiogenesis and EC–cardiomyocyte interactions. Emerging evidence indicates that SIRT3 is involved in the regulation of endothelial metabolism and angiogenesis and thus affects the development of cardiovascular diseases associated with aging. This review will discuss the current knowledge of SIRT3 and its functional role on endothelial metabolism, cardiac function, and cardiovascular diseases. Abstract : Emerging evidence indicates that SIRT3 is involved in the regulation of endothelial metabolism and angiogenesis and thus affects the development of cardiovascular diseases associated with aging and hypertension. This review will discuss the current knowledge of SIRT3 and its functional role on endothelial metabolism, endothelial–cardiomyocyte interactions, cardiac function, and cardiovascular diseases.